2010
DOI: 10.1016/j.paid.2010.07.021
|View full text |Cite
|
Sign up to set email alerts
|

The role of Gray’s revised RST in the P–psychopathy continuum: The relationships of Psychoticism with a lack of fear and anxiety, and increased impulsivity

Abstract: Gray's revised Reinforcement Sensitivity Theory (rRST; Gray & McNaughton, 2000) may play a role in explaining deficits in Psychoticism (P) and psychopathy (Corr, 2010). In this paper, we examine the relationships of P with anxiety, fear, impulsivity and reward reactivity in normal populations to assess whether these associations mirror the hypothesized role of RST motivations in psychopathy. Two hundred and twelve participants completed measures of Psychoticism, impulsivity and rRST motivations (BIS-anxiety, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 35 publications
1
23
0
1
Order By: Relevance
“…While the findings generally support Eysenck's P-psychopathy continuity hypothesis, the differential associations of the P-facets with criterion measures suggest that they may be more useful in predicting primary and secondary psychopathic tendencies than overall P. Specifically, the associations of primary P traits with reduced empathy may explain inconsistencies in the literature concerning how global P is linked to primary psychopathy (Hare, 1982;Heym & Lawrence, 2010), and questions the broad association of the higherorder dimension P with primary psychopathy. Moreover, the opposite associations of the Pfacets with affective and cognitive components of aggression may explain the lack of associations of overall P with anger or hostility in the current and previous research (Wood & Newton, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the findings generally support Eysenck's P-psychopathy continuity hypothesis, the differential associations of the P-facets with criterion measures suggest that they may be more useful in predicting primary and secondary psychopathic tendencies than overall P. Specifically, the associations of primary P traits with reduced empathy may explain inconsistencies in the literature concerning how global P is linked to primary psychopathy (Hare, 1982;Heym & Lawrence, 2010), and questions the broad association of the higherorder dimension P with primary psychopathy. Moreover, the opposite associations of the Pfacets with affective and cognitive components of aggression may explain the lack of associations of overall P with anger or hostility in the current and previous research (Wood & Newton, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, Heym and Lawrence (2010) showed that raised levels of P in normal populations were associated with reduced anxiety and punishment sensitivity -a hallmark of primary psychopathy, and increased impulsivity similar to secondary psychopathy; suggesting that P taps into aspects of both primary and secondary psychopathy in normal populations. Such inconsistent findings may be explained by a multi-faceted nature of P.…”
Section: Psychopathy and Its Componentsmentioning
confidence: 99%
“…Thus, reward processing and goal-directed behavior may play a differential role in pure Attention Deficit or Hyperactivity Disorder. Moreover, BASreward responsiveness and BAS-drive cluster under a reward reactivity factor that is distinct from a trait impulsivity factor, which encompasses BAS-fun seeking (Smillie, Pickering, & Jackson, 2006;Heym & Lawrence, 2010). Given this distinction between reward reactivity and trait impulsivity, the current findings question a simple overactive BAS account (if conceptualized as reward sensitivity rather than impulsivity) in ADHD and may explain inconsistent findings in the past (Oosterlaan & Sergeant, 1998;Paloyelis et al, 2009).…”
Section: Discussionmentioning
confidence: 64%
“…It is possible that some impulsive aspects are driven by hypersensitivity to aversive cues leading to fight/flight responses. Indeed, high levels of FFFS have been shown to increase (moderate) trait impulsivity (Heym & Lawrence, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…BAS fun seeking refers to impulsive approach of rewards and sensation seeking, BAS drive refers to the persistent pursuit of desired goals, and BAS reward responsiveness refers to the positive response to reward. Recent studies suggested that BAS fun seeking is more closely linked to rash impulsiveness, while BAS drive and reward responsiveness are more closely related to reward sensitivity (Heym & Lawrence, 2010;Leone & Russo, 2009;Smillie, Jackson, & Dalgleish, 2006). For example, BAS fun seeking has been found to have substantial positive correlations with impulsive behaviors such as drug and alcohol abuse in both clinical and community samples (Alloy et al, 2009;Franken & Muris, 2006;Johnson, Turner, & Iwata, 2003).…”
Section: Introductionmentioning
confidence: 99%